Numerical analysis in rock engineering 1 - Yang, Wei Xuan (2014)
The rock support and reinforcement are an important area of analysis for underground rock cavern analysis for safe construction in a space constrained society today. The objective of this report is to evaluate the effects of rock bolt on rock cavern stability using the Discontinuous Deformation Analysis (DDA).